Thermal properties and morphologies of poly(ethylene terephthalate) in blends with epoxidized natural rubbers / Siti Farehah Suliman @ Sulaiman - Suliman @ Sulaiman, Siti Farehah (2010)
Thermal properties and morphologies for polymer blends of poly(ethylene terephthalate) (PET) and epoxidized natural rubber with 25 mole % (ENR-25) and 50 mole % epoxy content (ENR-50) were studied by using differential scanning calorimeter (OSC) and polarizing optical microscope (POM). The blends were prepared by precipitation method. Immiscibility of the components is revealed by observation of two glass transition temperatures (Tg) that correspond to that of the neat constituents. Equilibrium melting points (Tmo) of PET in blends was determined by app lying Hoffman-Weeks step-wise annealing procedure. The Tmo of neat PET and PET in the blends are around 260 °C. The degree of crystallinity of PET in blends with ENR-25 and ENR-50 remains constant. The rate of crystallization of PET in blends is characterized by the reciprocal half time (t0.5-1). It displays an Arrhenius-like behavior with respect to temperature and it stays constant at isothermal crystallization temperature, Tc = const as long as PET is in excess. Rate of crystallization of PET in the blends decreases exponentially as the Tc increases. Dispersed phase of ENR-25 and ENR-50 in the matrix of PET can be observed when the content of PET in excess.